Enzyme engineering: Reshaping the biocatalytic functions - Ali, Misha; Ishqi, Hassan Mubarak; Husain, Qayyum (Biotechnology and bioengineering, 2020)
Enzyme engineering is a powerful tool to fine‐tune the enzymes. It is a technique by which the stability, activity, and specificity of the enzymes can be altered. The characteristic properties of an enzyme can be amended by immobilization and protein engineering. Among them, protein engineering is the most promising, as in addition to amending the stability and activity, it is the only way to modulate the specificity and stereoselectivity of enzymes. The current review sheds light on protein engineering and the approaches applied for it on the basis of the degree of knowledge of structure and function of enzymes. Enzymes, which have been engineered are also discussed in detail and categorized on the basis of their respective applications. This will give a better insight into the revolutionary changes brought by protein engineering of enzymes in various industrial and environmental processes. Revolutionary advancement in bio‐catalytic functions brought by enzyme engineering is discussed in this review. An effort has been made to throw light on engineered enzymes which have been modulated to enhance their stability, activity and specificity to make their efficient use in industrial and environmental processes. Also, the authors have described the strategies being used for enzyme engineering on the basis of degree of knowledge of structure‐function relationship.